2019
DOI: 10.1002/eat.23039
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of brief cognitive behavioral therapy for eating disorders: A qualitative investigation

Abstract: Objective Although it is important to analyze the effectiveness of new therapies, it is also necessary to consider how patients experience them. This is particularly important if we are to maximize treatment acceptability and reduce attrition. This study examined patient experiences of a new 10‐session cognitive‐behavioral therapy (CBT‐T), using a qualitative approach. Method The sample was 17 patients with a diagnosis of bulimia nervosa who had received CBT‐T (including treatment completers and non‐completers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Nor did the study examine the perspectives of patients and therapists on their experiences of this group format (e.g., greater group cohesion/support; anxiety about letting down other group members). Future research into group CBT‐T should involve a qualitative arm, to determine whether patient experience reflects that in individual CBT‐T (Hoskins et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nor did the study examine the perspectives of patients and therapists on their experiences of this group format (e.g., greater group cohesion/support; anxiety about letting down other group members). Future research into group CBT‐T should involve a qualitative arm, to determine whether patient experience reflects that in individual CBT‐T (Hoskins et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This could be seen by a low drop‐out rate (below 3%) and the patients' willingness to take part in the discussion and debriefing group. It has been suggested that it is highly important to consider how patients experience therapies and to maximize treatment acceptability (Hoskins et al, 2019). Embodiment interventions such as power posing appear to receive interest from the patients and could potentially be a good pathway toward dialogue about self‐perception and body‐perception.…”
Section: Discussionmentioning
confidence: 99%
“…ARFID risk factors T24 Family-based treatment Family-based treatment: Where are we and where should we be going to improve recovery in child and adolescent eating disorders [77] T15 ARFID Development of the Pica, ARFID, and Rumination Disorder Interview, a multi-informant, semi-structured interview of feeding disorders across the lifespan: A pilot study for ages 10-22 [78] T47 Parental impact The relationship between parent feeding styles and general parenting with loss of control eating in treatment-seeking overweight and obese children [79] T16 Pregnancy Documenting the course of loss of control over eating prior to, during and after pregnancy among women with pre-pregnancy overweight and obesity [80] Stand-alone T23 Recovery # recovery: Understanding recovery from the lens of recovery-focused blogs posted by individuals with lived experience [81] T26 Network analysis Network analysis: An innovative framework for understanding eating disorder psychopathology [82] T28 Perfectionism Stress situation reveals an association between perfectionism and drive for thinness [83] T37 Genetics Twin studies and the etiology of eating disorders [84] T39 Physical activity Monitoring eating and activity: Links with disordered eating, compulsive exercise, and general wellbeing among young adults [85] T41 Stigma Interventions to reduce the stigma of eating disorders: A systematic review and meta-analysis [86] T45 Medication Bulimia nervosa treatment: A systematic review of randomized controlled trials [87] T2 Cognitive-behavioral Patients' experiences of brief cognitive-behavioral therapy for eating disorders: A qualitative investigation [88] T12 Personality Relationships among attachment styles, personality characteristics, and disordered eating [89] T13 Self-shame Within-persons predictors of change during eating disorders treatment: An examination of self-compassion, self-criticism, shame, and eating disorder symptoms [90] 3.3.2. Research Topic Network Some topics tended to have overlapped themes and characteristics.…”
Section: Group Label Topic Name Representative Article: Title (Refere...mentioning
confidence: 99%